Kebijakan Jepang dalam Mengantisipasi Klaim Air Defense Indentification Zone (ADIZ) oleh Tiongkok - Inggrid Gabriela; Tri Cahyo Utomo (Journal of International Relations Diponegoro, 2018)
Air Defense Identification Zone (ADIZ) is an air transportation identification system thatapplied by a country to protect their zone. China ratified ADIZ in November 2013 as oneform of defense and security of the country. China ADIZ became an issue because theidentification zone claimed by China covers some of the surrounding country’s area. Oneof the area is Senkaku Island which under the administration of Japan. This research aimsto know what policies are made by Japan in anticipation of ADIZ claims by China. Thisresearch uses political realism theory in understanding the reason of Japan’s policiesregarding ADIZ. The results showed that the policy is a form of the realization of itsnational interest, where Japan are strengthening their own defense and security.